Perbandingan Algoritma Horspool dan Algoritma Zhu-Takaoka dalam Pencarian String Berbasis Desktop - Adhi Kusnadi; Abraham Khrisnandi Wicaksono (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2017)
String searching is the search process by using the index to find text that can help in information retrieval systems. Continuing previous research, this study uses an algorithm Horspool and Zhu-Takaoka to find the performance of each of these algorithms in the search for a pattern in the text. So they make a useful desktop-based application to measure performance of both algorithm, particulary the time required to perform string searching process. Using the method of prototyping and Microsoft Visual Studio with C# programming language implementation. Result obtained from this application is the number of words found, and the processing time of each algorithm. From this study, the Horspool algorithm is 19,82845 percent faster in first test with the pattern